Great debates in medical law and ethics - Goold,Imogen (Palgrave great debates in law, 2018)
An engaging introduction to the fascinating debates surrounding medical law and ethics, providing a cutting edge for students who are looking to gain additional insights with which to excel. Readers are introduced to the many concepts and debates surrounding each core area and presented with the key tensions and questions underlying each topic.